INOVASI DHARMADUTA FO GUANG SHAN: TRANSFORMASI PEMBINAAN CARA BERPIKIR BERUCAP DAN BERTINDAK DI ERA DIGITAL - Oktavia Mudhita Wulandari; Widia Darma; Yatno, Tri (Inisiasi, 2025)
This study examines the strategies of the modern Dharmaduta Fo Guang Shan  in actualizing Dharma as a source of social and humanitarian harmony. Using a sociocultural approach, this study highlights three main aspects: family education as a space for internalizing kusala kamma (good thinking, good speech, and good deeds), arts and culture as a means of engaging the younger generation, and the use of digital technology as a medium for disseminating Dharma. These practices demonstrate the transformation of Buddhist teachings from ritualistic forms to concrete humanitarian practices that adapt to changing times. From the perspectives of Durkheim, Geertz, Bourdieu, and Habermas, Fo Guang Shan  activities represent the embodiment of social solidarity, shared understanding of cultural meanings, internalization of values, and symbolic communication across generations. Dharma is no longer confined to the realm of worship but is present in everyday life as an art of living that fosters virtue, compassion, and peace. The results of this study confirm that Humanist Buddhism is able to address global challenges through harmonious social and spiritual innovation, making Dharma a force for universal social harmony.